1983
DOI: 10.1161/01.cir.68.2.360
|View full text |Cite
|
Sign up to set email alerts
|

Determination of anaerobic threshold for assessment of functional state in patients with chronic heart failure.

Abstract: The use of anaerobic threshold in assessment of aerobic capacity was evaluated in 34 normal subjects and 47 patients with various kinds of chronic heart disease. Anaerobic threshold was determined as the oxygen consumption (W02) at which a linear relationship between pulmonary ventilation (yE) and V02 was lost during progressive treadmill exercise. Anaerobic threshold determined in this manner was validated with that determined by blood lactate measurements in eight normal subjects and nine cardiac patients (r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
76
0
2

Year Published

1986
1986
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(83 citation statements)
references
References 18 publications
5
76
0
2
Order By: Relevance
“…In the present patients, the anaerobic threshold occurred at a higher percentage of peak V9O 2 than in normal subjects. This has been previously noted in PPH [4], CHF [19] and older patients with various diseases associated with a decrease in peak V9O 2 [20]. It may be explained by the slower rise in V9O 2 above the anaerobic threshold and by the fact that resting V9O 2 already represents a considerable proportion of peak V9O 2 [4].…”
Section: Discussionsupporting
confidence: 60%
“…In the present patients, the anaerobic threshold occurred at a higher percentage of peak V9O 2 than in normal subjects. This has been previously noted in PPH [4], CHF [19] and older patients with various diseases associated with a decrease in peak V9O 2 [20]. It may be explained by the slower rise in V9O 2 above the anaerobic threshold and by the fact that resting V9O 2 already represents a considerable proportion of peak V9O 2 [4].…”
Section: Discussionsupporting
confidence: 60%
“…Many investigators have recently used the anaerobic threshold measurement to estimate the degree of cardiovascular impairment25-8 and effectiveness of therapy.22 '23 In general, the magnitude of the anaerobic threshold reduction has correlated well with the degree of hemodynamic abnormality. 5,7,8 Recent studies13-15 have suggested that the ejection fraction during exercise increases compared with rest in normal persons but does not change or decreases in patients with heart disease (particularly coronary artery disease). However, only a few investigators evaluated the change of the ejection fraction below and above the anaerobic threshold.…”
Section: Discussionmentioning
confidence: 99%
“…In HF patients, the validity of ventilatory methods is questioned, because of difficulties in detecting AT 1,6,12,14,26 in this population, and because of the inherent subjectivity of the visual analysis. 8 In a study conducted by Matsumara et al 16 , a highly reproducible AT detection was observed in a mixed population of healthy subjects and HF patients, by examining graphically the relationships between minute ventilation and VO 2 . The present study was conducted with a sample composed exclusively of individuals with HF, and the techniques of choice for AT detection were based on VCO 2 analysis 6,14,26 .…”
Section: Discussionmentioning
confidence: 99%
“…AT detection by ventilatory methods is considered valid 5,14,16,25 and in healthy subjects and athletes, it has proven to be highly reproducible 5,25 . In HF patients, the validity of ventilatory methods is questioned, because of difficulties in detecting AT 1,6,12,14,26 in this population, and because of the inherent subjectivity of the visual analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation